Synergetic Effects of Combined Treatment of Colistin With Meropenem or Amikacin on Carbapenem-Resistant Klebsiella pneumoniae in vitro - Yu, Lan; Zhang, Jisheng; Fu, Yanjun; Zhao, Yongxin; Wang, Yong; Zhao, Jing; Guo, Yuhang; Li, Chunjiang; Zhang, Xiaoli (Frontiers in Cellular and Infection Microbiology, 2019)
The purpose of this study was to investigate the synergistic and bactericidal effects of combinations of colistin with meropenem or amikacin in vitro and provide laboratory data needed for development of therapeutic strategies for the treatment of carbapenem-resistant Klebsiella pneumoniae (CRKP) infection. We found that minimum inhibitory concentration (MIC) of colistin, meropenem and amikacin were 2~32, 4~256, and 1~16384 μg/ml, respectively. The minimum bactericidal concentration of the antibiotics was either 1× or 2×MIC. Treatments of 6 CRKP isolates at 1 μg/ml colistin completely killed 2 of them and suppressed 4 others growth. 4 CRKP isolates at 16 μg/ml meropenem or amikacin completely killed and suppressed 2 others growth. 2 CRKP isolates showed synergic effects in all colistin combination and 3 CRKP isolates showed synergic effects in part of colistin combination. Our data suggest that colistin in combination with either meropenem or amikacin could be a valid therapeutic option against colistin-resistant CRKP isolates. Moreover, the combination of colistin-amikacin is less expensive to treat CRKP infections in Eastern Heilongjiang Province.